Dobutamine stress echocardiography during covid-19 pandemic: impact on volume and positivity rates in a tertiary hospital. (4th February 2022) - Dimitroglou, Y; Kalompatsou, A; Tsartsalis, D; Giannoulis, E; Koukos, M; Solomou, E; Angelis, A; Patsourakos, D; Valatsou, A; Zisimos, K; Fragkoulis, C; Christofi, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The emergence of coronavirus 2019 infection (covid-19) was accompanied by severe social and economic restrictions and applied significant pressure to the healthcare systems. The first pandemic wave started in March to May 2020 and was characterized by the peak of confinement measures and lockdown application. The second wave started in September and peaked in November to December 2020 and was characterized by improved healthcare organization but significant burden for the hospitals and intensive care units. Dobutamine stress echocardiography (DSE) is used for evaluation of ischemia in patients with known or suspected coronary artery disease. Purpose: To compare DSE volume and positivity rates between 2019 and 2020 time periods in a department of a public tertiary hospital. Methods: We retrospectively analysed DSE studies performed in our department in 2020 including the peak of covid-19 restrictions and compared the data to the 2019. Results: Volume of DSE studies decreased from 1516 in 2019 to 996 in 2020 (-34.3%). The study volume reduction was greater in April (-93.7%) and May (-54.5%) when the covid-19 restrictions were at the peak. Great decreases were also recorded in November (-46.8%) and December (-53.5%) when the second wave of covid-19 disease emerged. Conversely, small increases were recorded in September (7.1%) and October (10.6%) (figure 1). Regarding positivity rates, a statistically non-significant increase was recorded (33.6% vs 34.2% in 2019 and 2020 respectively, p = 0.73). Interestingly a statistically significant increase in positivity levels was recorded during the period March to May 2020 compared to the same period of 2019 (44.7% vs 36.9%, p = 0.029). On the contrary, positivity rates were decreased at the period September to December (27.1% vs 34.2%, p = 0.019) (figure 2). Conclusions: Volume of DSE studies was significantly reduced in 2020 when compared to 2019 during respective peaks of the pandemic and the accompanying restriction measures. Positivity rates were higher during the first pandemic wave, possibly due to decreased hospital attendance of mildly symptomatic patients in combination with stricter admission criteria at the emergency department. Lower positivity rates during the second pandemic wave possibly reflect an adjustment of both healthcare systems and patients to the new conditions imposed by the covid-19 pandemic.